Issues and challenges in voltage uprating for sustainable power operation: A case study of a 132 kv transmission line system in malaysia - Nor S.F.M.; Ab Kadir M.Z.A.; Ariffin A.M.; Osman M.; Rahman M.S.A.; Zainuddin N.M. (MDPI, 2023)
demand-side management; electrical power; electricity supply; exploration; forest cover; infrastructure planning; transportation development; Malaysia